2008
DOI: 10.1016/j.cell.2007.12.040
|View full text |Cite
|
Sign up to set email alerts
|

Active Caspase-1 Is a Regulator of Unconventional Protein Secretion

Abstract: Mammalian cells export most proteins by the endoplasmic reticulum/Golgi-dependent pathway. However, some proteins are secreted via unconventional, poorly understood mechanisms. The latter include the proinflammatory cytokines interleukin(IL)-1beta, IL-18, and IL-33, which require activation by caspase-1 for biological activity. Caspase-1 itself is activated by innate immune complexes, the inflammasomes. Here we show that secretion of the leaderless proteins proIL-1alpha, caspase-1, and fibroblast growth factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
660
3
19

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 781 publications
(699 citation statements)
references
References 49 publications
17
660
3
19
Order By: Relevance
“…Keratinocytes express large amounts of pro-IL-1a, which is biologically active without further processing. It is released upon cell lysis and can be secreted after inflammasome activation 39,44 . IL-1 can act in an autocrine manner, and its release by dying keratinocytes can stimulate further IL-1 production 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Keratinocytes express large amounts of pro-IL-1a, which is biologically active without further processing. It is released upon cell lysis and can be secreted after inflammasome activation 39,44 . IL-1 can act in an autocrine manner, and its release by dying keratinocytes can stimulate further IL-1 production 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Caspase-1 is the enzyme responsible for the maturation and release of IL-1b and IL-18. It is worth noting that caspase-1 also participates in the secretion of IL-1a, biologically active without any need for proteolytic processing [18]. Alum activated NLRP3 directly upon phagocytosis [14,17] without any intermediary role for the danger signals MSU and ATP [14,15,17].…”
mentioning
confidence: 99%
“…Brefeldin A treatment did not inhibit PARK7 secretion (Figure 2(C)), confirming that 6-OHDA-induced PARK7 secretion was mediated via an ER-/Golgi-independent secretory pathway. Because it had recently been reported that CASP1 (caspase 1) may act as regulator of unconventional protein secretion [34], we decided to assess the respective effects of a pan-caspase inhibitor (zVAD; i.e., Z-VAD[OMe]-FMK) and a specific CASP1 inhibitor (YVAD; i.e., Ac-YVAD-CMK) on PARK7 secretion. Our results indicated that 6-OHDA-induced PARK7 secretion was inhibited by either inhibitor (Figure 2(D)).…”
Section: Resultsmentioning
confidence: 99%